2022
DOI: 10.1371/journal.pone.0266363
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the attitude and problem-based learning in mathematics through PLS-SEM modeling

Abstract: Mathematics plays a leading part in day-to-day life and has enhanced a necessary component for human accomplishments. Students from many countries do not reach the expected level in mathematics. Therefore, it is essential to pay close consideration to the causes related to ability in mathematics. Mathematics attitude is considered as one of the critical variables in the process of mathematics learning. This study aimed to determine students’ attitudes and achievements through problem-based learning in mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The path coefficient results of this research are shown in Table 8. The results suggest that all four hypotheses are positive and statistically significant at a 0.05 significance level (Zamir et al , 2022). Specifically, the implementation of NFC is positively related to AM ( β = 0.495, p < 0.05, t > 1.645), CE ( β = 0.604, p < 0.05, t > 1.645), OE ( β = 0.492, p < 0.05, t > 1.645) and defence on Covid-19 ( β = 0.396, p < 0.05, t > 1.645).…”
Section: Discussionmentioning
confidence: 92%
“…The path coefficient results of this research are shown in Table 8. The results suggest that all four hypotheses are positive and statistically significant at a 0.05 significance level (Zamir et al , 2022). Specifically, the implementation of NFC is positively related to AM ( β = 0.495, p < 0.05, t > 1.645), CE ( β = 0.604, p < 0.05, t > 1.645), OE ( β = 0.492, p < 0.05, t > 1.645) and defence on Covid-19 ( β = 0.396, p < 0.05, t > 1.645).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, this resource is the best and most user-friendly method for analyzing and testing a theory [6,7]. The literature has underlined that although Amos is under CB-SEM, somehow it can handle analysis of PLS-SEM [124]. Although SmartPLS and Amos dominated among other software packages in mathematics education, Lisrel, Mplus, R package (Plpsm), and WarpPLS still have different strengths, special features, areas of improvement, estimation methods, and limitations that could influence a researcher's choice.…”
Section: Discussionmentioning
confidence: 99%
“…That study's results revealed that the majority of participants increased their confidence and their positive attitudes toward mathematics by the end of the study. In addition, a study conducted by Zamir et al (2022) on determining students' attitudes and achievements through problem based learning, revealed that mathematics attitude is considered as a critical element in the process of mathematics learning. Confidence in learning mathematics and mathematics motivation had a significant role in the students' attitudes toward problem based learning.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce mathematics anxiety, educators must focus less on speed tests (Reys et al, 1995). Instead, they have to focus more on adopting new teaching methods that are conformable to mathematics (Zamir et al, 2022). Additionally, mathematics teachers must make mathematics an enjoyable subject by using a meaningful method of teaching, and they must also explain the importance of mathematics to everyday life and to students' future careers (Cruikshank & Sheffield, 1992).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%